PENGARUH PENYIANGAN TERHADAP KUALITAS DAN PRODUKSI TANAMAN BAYAM HORENSO (Spinacia oleracea) The Effect of Weeding on the Quality and Yield of Horenso Spinach (Spinacia oleracea) - Norman Isna Rozaqi; Suci Nur Utami, Khusnul Khotimah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to determine the effect of weeding on the quality and yield of horenso spinach (Spinacia oleracea) cultivated at Agri Center Miyakonojo, Miyazaki, Japan. The research was conducted using two treatments without weeding and with weeding each on a plot of 10,000 m². Observed parameters included leaf color, leaf shape, leaf damage level, total harvest weight, and farm income analysis. The results showed that weeding had a significant positive effect on the quality of horenso spinach leaves. In the weeding treatment, leaf color remained bright green and glossy until the third month, leaf shape was broad and symmetrical, and leaf damage was minimal. Conversely, without weeding, leaf color tended to become dull/yellowish, leaf shape became smaller and uneven, and leaf damage levels were high. In terms of quantity, the weeding treatment yielded a total harvest weight of 240,000 kg (24 kg/m²), while the non-weeding treatment produced only 60,000 kg (6 kg/m²). Economic analysis indicated that the total revenue (TR) for the weeding treatment reached ¥1,320,000,000 with a net income of ¥1,309,673,780, whereas the non-weeding treatment had a TR of ¥330,000,000 with a net income of ¥319,935,780. This study concludes that weeding not only improves the quality and quantity of production but also provides substantial economic benefits. Therefore, weeding is recommended as an essential cultivation practice to enhance horenso spinach farm productivity